Utilization of water lily activated charcoal as a biofilter in tofu wastewater treatment - Noor Khamidah; Muhammad Imam Nugraha; Novita Kurnia Sari (Universitas Lambung Mangkurat, 2023)
The purpose of this study was to determine the effect of water lily activated charcoal as a biofilter in tofu wastewater treatment and to determine the effective dose of water lily activated charcoal as a biofilter in tofu wastewater treatment. The results showed that water lily activated charcoal can be used to improve the quality of tofu liquid waste; thus, it can improve the quality of tofu liquid waste which can be seen from the parameters of TSS (Total Suspended Solid). The treatment dose of 2 g of activated charcoal (A3) is the best dose to improve the quality of tofu liquid waste and has complied with the 2014 LH regulation concerning the quality standards of wastewater for the tofu industry, namely the parameters of TSS. The existence of this research can be a reference for further similar research by utilizing organic matter as an alternative in tofu wastewater treatment.